Business Model Canvas for Bananania MSMEs - Mirah, Sofyani (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
Since Covid 19 hit in 2020 – 2022, the growth of MSMEs has increased rapidly, with full support from the government, MSMEs have also grown, and competition in the food and beverage business is currently very competitive, for this reason Bananania feels that it must have a good business model canvas so that Bananania's business can grow rapidly. The current problem is that there are many products produced by Bananania (banana chips, banana granola, banana flour, banana cookies, frozen fried bananas and also banana rambak) so with a good canvas business model you will be able to sort out the problems, especially in the target segment. and also key activities so that the business can run smoothly. This research uses the Business Model Canvas (BMC) as a measuring tool to see how the business model is currently running, namely by using the 9 elements contained in the Business Model Canvas, and this business model can quickly describe how this business runs.